PEMBATALAN KEPUTUSAN WALI NAGARI SILAUT DITINGKAT PENGADILAN TATA USAHA NEGARA (STUDI PUTUSAN NOMOR: 54/G/2022/PTUN.PDG) - Zakir, Fauzan (Ensiklopedia Research and Community Service Review, 2025)
Abstract: The involvement of BAMUS in Nagari Government affairs is an important thing to do because BAMUS is a representative of the Nagari community. BAMUS is a form of democracy in the Nagari government which accommodates and channels all community aspirations for the progress of Nagari. The positions of BAMUS and Wali Nagari in the Nagari Government are equal because they were both elected by the community, and both appointed by the Regent. Therefore, BAMUS and Wali Nagari are institutions at the same level, so that to carry out BAMUS' supervisory function, BAMUS and Wali Nagari need to coordinate so that BAMUS can supervise the performance of Wali Nagari in a coordinated manner and all the information needed by BAMUS for supervision purposes can be obtained easily. In the process, the Defendant's exception was not accepted, explaining the following: Granted the Plaintiff's claim in its entirety. Declaring the cancellation of the State Administrative Decree, namely: 1) Decree of the Mayor of Nagari Silaut Number: 140/40/Kpts/WNS/VIII-2022 concerning the Appointment of Bamus Nagari Silaut Staff, Silaut District, Fiscal Year 2022, dated 18 August 2022; 2) Decree of the Mayor of Nagari Silaut Number: 140/34/Kpts-WNS/VIII-2022 concerning the Appointment of the Head of Administrative and General Affairs of Nagari Silaut, Silaut District, Pesisir Selatan Regency, dated 18 August 2022. Requiring the Defendant to revoke the State Administrative Decree, namely: 1) Decree of the Wali of Nagari Silaut Number: 140/40/Kpts/WNS/VIII-2022 Concerning the Appointment of Staff for Bamus Nagari Silaut, Silaut District, Fiscal Year 2022, dated 18 August 2022; 2) Decree of the Guardian of Nagari Silaut Number: 140/34/Kpts-WNS/VIII-2022 concerning the Appointment of the Head of Administrative and General Affairs of Nagari Silaut, Silaut District, Pesisir Selatan Regency, dated 18 August 2022.Keywords: Judge's considerations, cancellation, decision, Wali Nagari, Silaut.